On the Issue of Environmental Forensic Subtheory - N. V. Mikhaleva (Теория и практика судебной экспертизы, 2022)
At this point many of the concepts of environmental forensics have been theoretically elaborated, however its subtheory is yet to be developed. The article addresses the concept and subject of the environmental forensic subtheory. The author demonstrates that the subject, object and tasks of environmental forensics are not accordingly the subject, object and tasks of the environmental forensic subtheory: within the framework of the subtheory the regularities of the general theory of forensic examination regarding the environmental investigations are revealed. The author also proposes the definition of the subject of the environmental forensic subtheory, establishes its place as a part of the theory of expert diagnostics.